KREASI IKLIM SEKOLAH MELALUI GERAKAN SEKOLAH MENYENANGKAN DI SD MUHAMAMMADIYAH MANTARAN - Rr. Khoiry Nuria Widyaningrum; Fitri Nur Mahmudah (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this study was to determine the creation of the school climate in Muhammadiyah Elementary School and the role of the Principal in creating this climate. The research method was carried out in a descriptive qualitative manner. Data retrieval is done by observation or observation as well as interviews with students, teachers and parents of students' guardians. The research instrument used in the form of a list of questions and observation sheets. Photo and video documentation is also done as a reinforcement bouquet. The results obtained from this study are the creation of the school climate in Muhammadiyah Elementary School Mantaran colored by the concept of a fun school movement whose main purpose is to instill character and make education more humane humans through program 1) Positive Environment Creation, 2) Character Education, 3) Learning based on project and problem solving, 4) School Conectednes. Based on the results of observations, the level of the type of climate at the Muhammadiyah Elementary School is classified as an open school climate and is a level of conducive climate. The role of the school principal in creating a school climate in Muhammadiyah Elementary School is among others: 1) Changing the teacher's mindset and parents' guardianship towards education that humanizes humans, 2) creating relationships and relationships between people with love and affection, 3) division of delegation of duties , 4) resolving conflicts as soon as possible so as not to disturb the comfort of work, 5) giving motivation (performance rewards, awards, teacher good stars etc.), 6) harmonizing and enriching the work environment and learning by creating positive environments both physical and non-physical, 7) The Cenectedness School program includes GSM networks, Parent Teaching, etc.